Spectroscopic disentanglement of the quantum states of highly excited Cu2 - M. Beck (Nature Portfolio, 2019)
Transition metals are at the basis of key processes in chemistry and biology but their complex electronic structures make understanding of their properties a challenge. Here the authors resolve individual spectral lines of Cu2 in the deep UV region by two-colour resonant four-wave mixing.